STUDY OF THALLIUM INTOXICATIONIN BROILER CHICKS - Majid, Hashim (Iraqi Journal of Science, 2024)
The study of thallium intoxication on 120 broiler chicken by using differentdoses of thallium, 0.2; .5 and 1.0 mg/kg. B.Wt. it was observed that the clinical sign,bloody diarrhea, appeared in the last ten days of the experiment. In second and thirdgroup the pathologic changes was hemorrhages and edema of skeletal muscles andbrain. Petechial hemorrhage in the testis, ovary and thyroid gland. Thehistopathological changes were comprised of hyperplasia, cellular, infiltration in thethyroid gland, narrow cortex of the ovary, in the brain there were remarkable edemawith perivascular cuffing and loss of purkinge cells in the cerebellum. The resultssuggest that thallium was accumulative.